Ratio Legis Phrase "Mandatory" in Government Regulation on Land Deed Making Officer As Protocol Recipient - Arianti, Rizki Diaswari Laila; Budiono, Abdul Rachmad; Masykur, Mohammad Hamidi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
The phrase “obligatory” in the government regulation regarding the Land Deed Official as the recipient of the protocol has significant legal implications in determining the nature of his/her obligations. The ratio legis of this phrase is important to assess whether the obligation is absolute or conditional, which affects legal certainty and uniformity of its application. This study uses a normative legal method, namely analyzing legal norms through the interpretation of relevant laws, regulations, and legal doctrines. This study relies on primary legal materials, including laws and government regulations; secondary legal materials, such as legal commentaries and scientific articles; and tertiary legal materials, including legal dictionaries and encyclopedias. Data collection was carried out through a literature study, which ensured a comprehensive examination of legal texts and academic discussions. This study aims to evaluate the extent to which the term “obligatory” imposes binding duties on the Land Deed Official in receiving and managing the protocol. The research findings indicate that the phrase “obligatory” reflects an imperative legal obligation based on the theory of legal positivism, which prioritizes compliance with written legal norms. However, from the perspective of the theory of legal certainty (Rechtszekerheid), the regulation is less clear in defining the procedural mechanism, resulting in inconsistent application among Land Deed Officials. This ambiguity poses challenges in enforcing uniform practices, potentially undermining the effectiveness of the regulation.